Energy-cost analysis of alternative sources to electricity in Nigeria (2012)
In this work, a comparative analysis of alternative energy sources has been carried out to ascertain their suitability in terms of availability, cost, advantages and disadvantages among other factors. The selected energy alternatives are solar and inverters. The first case study-site was an office suit located in government reserved area and the second a medium house unit within Lagos the most commercial city in Nigeria. Practical surveys and data collection were carried out for the selected sites coupled with their energy auditing to obtain the total energy consumed. An energy sizing analysis helped in determining the energy specifications and installation-cost of the alternative energy sources in the surveyed sites. The results obtained presented guiding principles among other solutions on how homes and offices canbe powered by applying the method of selective-loading to reduce energy cost.